The construction of identity in African American fiction: female resistance in Song of Solomon - Germani, Miriam Patricia (2006)
The end of the totalising discourses of the great modern metanarratives has produced a displacement of fixed definitions of identity. Thus, a space for the recognition of difference has been created in which formerly silenced groups –the colonized, minority populations, women– have been able to voice their histories and experiences in an attempt to reinforce their cultural bonds and the values of their ancestral cultures as a means of resistance to the colonialist ideology (Sarup, 1996:101). Within this context, postcolonial narratives –such as the fiction produced by African-American women writers– have become an instrument of cultural transmission for historically subjugated peoples. Furthermore, they constitute a means of defiance and challenge to the values of the hegemonic society that oppresses them. The aim of the present work is to show how Toni Morrison constructs the identity of the main female character in her novel Song of Solomon and how she empowers her to become a symbol of resistance. The novel is approached from a postcolonial and cultural perspective in an attempt to analyse the reactions to colonialism as they are represented in contemporary African-American fiction.